Dexamethasone Otoprotection in a Multidose Cisplatin Ototoxicity Mouse Model. (14th November 2013) - Hughes, Amy Lawrason; Hussain, Nighat; Pafford, Ryan; Parham, Kourosh
Abstract : Objective: To develop a murine model for multidose administration of cisplatin that produces significant hearing threshold elevations and to use this model to assess the protective properties of intratympanic (IT) dexamethasone against cisplatin ototoxicity. Study Design: Controlled repeated measures design. Setting: Translational research laboratory. Subjects and Methods: Intraperitoneal (IP) cisplatin, 2 or 3 mg/kg/day, was administered for a total of 5 or 10 days in young CBA/J mice. Pure‐tone evoked auditory brainstem response (ABR) thresholds were performed on days 7, 14, 21, and 28 to evaluate hearing threshold shifts. After development of the optimal dosing regimen, 15 mice received IT dexamethasone (24 mg/ml) in one ear and IT saline in the contralateral ear. Results: Significant threshold elevations were obtained for the 2 and 3 mg/kg/day 10 day groups, but both had high mortality rates and were excluded as potential multidose murine models. The 3 mg/kg/day 5 day group had a lower mortality rate and significant ABR threshold elevations for all frequencies on days 7, 14, 21, and 28. Using this dosing model, no statistically significant difference between IT dexamethasone and saline treated ears was found. Conclusions: Unlike previous single dose models, IT dexamethasone did not have an otoprotective effect in a multidose murine model of cisplatin ototoxicity.